Peer review report 2 on "Outcomes of liver resection for haemorrhagic hepatocellular adenoma". (January 2016) - Darnis, Benjamin
Abstract: Intro: The study does not evaluate the outcomes for hepatectomy performed in an emergency setting, but surgery for adenomas who have bled, whatever the delay between the bleeding and the surgery. The justification of this study is not right. Methods: There is no need of 2 names for each group (choose between group 1 or RHCA; and between group 2 or NRHCA). Results: there was no death. Conclusions: you can't conclude about emergency liver resection if you don't write about it in the results section.